Corneal Laceration Repair! - Prateek Jain; Anshuman Pattnaik (Delhi Journal of Ophthalmology)
Ocular trauma is an emergency which should be addressed immediately. Injury to cornea is a preventable cause of blindness. A meticulous corneal tear repair is essential for optimal visual outcome. This photo essay aims to brief postgraduate residents with an insight on principles of full thickness corneal tear repair. Two cases of severe penetrating corneal injury are presented here who were operated with satisfactory restoration of ocular integrity